ENVIRONMENTAL HISTORY OF THE DRY FOREST BIOME OF GUERRERO, MEXICO, AND HUMAN IMPACT DURING THE LAST C. 2700 YEARS - Berrio Ju.C.; Hooghiemstra H.; van Geel B.; Ludlow-Wiechers B. (My University, 2006)
Two lake sediment cores from Madre del Sur mountain range,Guerrero State, west-central Mexico were studied to examine the pastdynamics of the dry forest biome. Pollen, spores of coprophilousfungi, cyanobacteria and lithological changes are presented. The390-cm Tixtla core (1730’N, 99°24W, 1400 maltitude) represents the last 2700 cal. yr; the 340-cm Huitziltepeccore (17°45N, 99°28W, 1430 m altitude) representsthe last 2050 cal. yr. Pollen shows climate-dependent competitionbetween dry deciduous forest (with Asteraceae, Chamaesyce-type,Bursera, Euphorbia, Myrica andLysiloma-Pithecellobium-type as main components) and moister(mesophyllous) forest (with Pinus, Quercus, Alnus andJuglans). Human impact on the environment is apparent duringthe entire record, as evidenced by crop cultivation (Zea mays,Amaranthus, Capsicum, Chenopodium), coprophilous fungi(Podospora-type and Sporormiella-type), deforestation (at Tixtla in particular) and lake eutrophication, ie, cyanobacteria blooms. Environmental change at both sites is summarized as follows. Period 1 (2700-2450 cal. yr BP): abundant dry deciduous forest and climate conditions drier than today. Period 2 (2450-1950 cal. yr BP): little change in proportions of dry deciduous and mesophyllous forest but floral composition of the forests differed between sites. Human occupation was low. Period 3 (1950-1550 cal. yr BP): dry deciduous forest decreased while mesophyllous forest increased, indicating more humid climatic conditions. Populations expanded significantly around 1950 cal. yr BP. Period 4 (1550-1070 cal. yr BP): maximum expansion of mesophyllous forest. Climate was more humid than today. Pre-Hispanic populations at Tixtla reached high numbers leading to deforestation and eutrophication. Period 5 (1070-c. 750 cal. yr BP): shows abundant mesophyllous forest and lowest proportions of dry deciduous forest. Climate continued to be humid. There is evidence of forest harvesting, crop cultivation and dense human population. Period 6 (c. 750-225 cal. yr BP): dry deciduous forest expanded and mesophyllous forest decreased. There was significant deforestation by pre-Hispanic people around Lake Tixtla. High population densities and frequent fires at both sites caused eutrophication of the lakes. Domesticated herbivores were introduced ?ad 1500 and the presence of dung is reflected in the record of coprophilous fungi. Period 7 (the last 225 calendar years): the basins were used intensively by local people and their cattle. Dry deciduous forest continued to increase while mesophyllous forest decreased.
Keywords: CLIMATE CHANGE; VEGETATION HISTORY; ENVIRONMENTAL HISTORY; HUMAN IMPACT; COPROPHILOUS FUNGI; DRY FOREST; GUERRERO; HOLOCENE; MEXICO; PRE-HISPANIC OCCUPATION; POLLEN; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен